2023-0288 Central, Eastern and South-Eastern Europe (CESEE) Bank Lending Survey - European Investment Bank (European Investment Bank, 2024)
The CESEE Bank Lending Survey is a unique instrument developed in the context of the Vienna Initiative to monitor cross-border banking activities and deleveraging in Central, Eastern and South-Eastern Europe. It serves to better understand the determinants/constraints influencing credit growth in the region and to gain forward-looking insights into the strategies of cross-border banks and market expectations regarding local financial conditions.This report presents the results of the EIB CESEE Bank Lending survey at the regional and single country levels.